Documents as context: rethinking the materiality of content and its impacts on knowledge organization - Guimarães, José Augusto Chaves [UNESP] (IBICT, 2023)
Organizing, recovering, preserving and making society’s memory available, in its most diverse aspects, has always permeated the knowledge and actions of humanity, which, over time, sought to build artifacts that could go beyond the limitations of human memory, in order to host an ever-increasing volume of data, information and knowledge. However, it was from the 19th century, after the information explosion, that the concern with organizing knowledge recorded in institutionally preserved documents intensified. In view of this, the indexical - or testimonial - character of documents is discussed, not only regarding their content, but, and, mainly, as a result of production, an aspect that will impact their organization. In this sense, the new configurations of documentary content – the core of knowledge organization – are analyzed, which go beyond this subject to add elements related to its provenance, organicity, authorship, as well as its space-time context.
O documento como contexto: repensando a materialidade de um conteúdo e seus impactos na organização do conhecimento
Keywords: documents; knowledge organization